2018
DOI: 10.2209/tdcpublication.2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking on Interleukin-34 Levels in Gingival Crevicular Fluid and Plasma in Periodontal Health and Disease: A Clinico-biochemical Study

Abstract: Interleukin-34 (IL-34), an alternative ligand for macrophage colony-stimulating factor receptor, plays an important role in osteoclastogenesis. The aim of this study was to analyze the effect of smoking on IL-34 levels in gingival crevicular fluid (GCF) and plasma in individuals with healthy periodontium and chronic generalized periodontitis (CP). A total of 60 individuals ranging in age from 25 to 55 years were enrolled in the study. The participants were divided into 4 groups: Group A, 30 samples (15 GCF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…GCF IL-34 levels decreased in all periodontitis groups at 6-week. This is consistent with the results of other studies with IL-34 (5,(32)(33).…”
Section: Discussionsupporting
confidence: 93%
“…GCF IL-34 levels decreased in all periodontitis groups at 6-week. This is consistent with the results of other studies with IL-34 (5,(32)(33).…”
Section: Discussionsupporting
confidence: 93%
“…Salivary and serum IL-34 levels were decreased significantly in smoker and non-smoker periodontitis patients after NSPT. These findings were in accordance with previous reports of altered levels of these markers in GCF (21,24,47) and serum (24,47) in periodontitis and decreased after NSPT (21,47). However, some studies reported that healthy controls showed higher IL-34 levels in saliva (48,49) and elevated after NSPT (49).…”
Section: Discussionsupporting
confidence: 93%
“…In RANKLinduced osteoclastogenesis, IL-34 can replace macrophage colony-stimulating factor (M-CSF) and promote osteoclast differentiation as M-CSF does. A recent study showed that serum and GCF IL-34 levels in smokers were higher than in non-smoker patients, which suggested that smoking may be an essential factor in releasing IL-34 (24). To our knowledge, no study that reported the relationship between smoking and the salivary IL-34 before and after NSPT.…”
Section: Introductionmentioning
confidence: 86%